Schlieren techniques for observations of long positive sparks: Review and application. (23rd June 2022) - He, Junjia; Wang, Xiankang; Zhao, Xiangen; Lee, Juhyeong; Du, Yaping; Liu, Xiaopeng; Gan, Quan; Liu, Yang; Liao, Yuqin
Abstract: Understanding the mechanism of positive leader discharge is important in lightning protection engineering and the external insulation design in high voltage power transmission systems. During the propagation of a positive leader, some processes without light‐emitting, for example, the insulation recovery process after the breakdown, cannot be observed by optical photography techniques. With the combination of the digital high‐speed imaging system, the conventional Schlieren techniques offer new vistas in the long air gap discharge observation. The important features of high spatial resolution, high sensitivity, and easy arrangement make Schlieren techniques powerful and effective tools for characterising the discharge processes without light‐emitting. This work presents a brief review of current Schlieren techniques and discusses the design of the Schlieren optics system for long spark observations. Several interesting phenomena discovered at different phases of long sparks with high‐speed Schlieren techniques are also presented.